Analisis Persepsi Masyarakat Nelayan Palabuhanratu Kabupaten Sukabumi Terhadap Rencana Pelaksanaan Kebijakan Penangkapan Ikan Terukur - Aulia Putri Kapsari Hafel; Asep Agus Handaka Suryana; Atikah Nurhayati Nurhayati; Ine Maulina (Jurnal Galung Tropika, 2025)
The government has issued Government Regulation (PP) Number 11 of 2023 concerning Measured Fishing (PIT), which was created to maintain the sustainability of resources and optimize the sector's economic benefits. The implementation of new policies generally receives varying responses from the public. This study aims to analyze the perceptions of the Palabuhanratu fishing community, Sukabumi Regency, West Java, regarding the planned implementation of the Measured Fishing policy. The study was conducted at the Palabuhanratu Archipelago Fisheries Port (PPN), Sukabumi Regency, West Java, from January to September 2024. Data collection was carried out using a descriptive and quantitative approach with three methods: observation, interviews, and documentation. The sample was determined by purposive sampling. Data analysis used a Likert scale scoring to analyze perceptions, validity, and reliability. The results showed that most fishermen in the Palabuhanratu PPN had a low understanding of the PIT policy. This low level of knowledge of fishermen impacts attitudes and perceptions that tend not to support the implementation of the PIT policy. The majority of fishermen feel that PIT policies, including zoning and catch quotas, have the potential to be detrimental, especially in terms of access to fish resources and income.